RANCANG BANGUN PERKAKAS RAGUM TANGAN SERBAGUNA - Saputra, Rifkia; Ramdani, Rizki (UPPM Politeknik TEDC Bandung, 2024)
Many forms of technology development aim to answer needed for human work efficiency. so an effective technology development effort is needed. Multifunctional hand vise tools are tools used to disassemble nuts and bolts in several sizes, open bottle caps, become hammers to hit nails and many others. Threads are the main component in multipurpose hand vise tools. Thread problems that often arise are jammed threads due to rust or worn paths due to the workpiece load. Threaded material uses St 42 which is able to support and suppress frictional loads and loads with pressure. Experiments were carried out by hitting nails, opening bottle caps, opening nuts & bolts, and holding threads that were easy to slide. The frame and chuck materials use stainless steel 304. The design of this Multifunctional hand vise tool is expected to be an industrial solution to streamline time and energy with these tools when used in small workshops or even in large industries.